2003
DOI: 10.1042/bj20030169
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of four glutathione transferase genes genetically linked to a major insecticide-resistance locus from the malaria vector Anopheles gambiae

Abstract: A cluster of eight genes encoding glutathione transferases (GSTs) are located on division 33B of polytene chromosome arm 3R of the African malaria mosquito, Anopheles gambiae. This region of the genome contains a major 1,1,1-trichloro-2,2-bis-( p -chlorophenyl)ethane (DDT)-resistance locus, rtd1. These GSTs belong to the insect-specific Epsilon class and share between 22.6 and 65.2% identity at the amino acid level. Two distinct allelic variants of the Epsilon GST, GSTe1, differing at 12 out of 224 amino acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 27 publications
5
141
1
6
Order By: Relevance
“…The insect-specific Delta-class and Epsilon-class GSTs are thought to be major contributors to detoxification and insecticide resistance (Ketterman et al 2011). In addition, some Epsilon-class GSTs in mosquito have peroxidase activity and may be important in protection against oxidative stress (Lumjuan et al 2005;Ortelli et al 2003). The insect Sigma-class and Theta-class GSTs are implicated in the detoxification of lipid peroxidation products, suggesting a protective role against oxidative stress (Singh et al 2001;Yamamoto et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The insect-specific Delta-class and Epsilon-class GSTs are thought to be major contributors to detoxification and insecticide resistance (Ketterman et al 2011). In addition, some Epsilon-class GSTs in mosquito have peroxidase activity and may be important in protection against oxidative stress (Lumjuan et al 2005;Ortelli et al 2003). The insect Sigma-class and Theta-class GSTs are implicated in the detoxification of lipid peroxidation products, suggesting a protective role against oxidative stress (Singh et al 2001;Yamamoto et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This GST is known for its ability to metabolize DDT in various mosquito species (Ortelli et al 2003;Lumjuan et al 2005), and recent studies confirmed its role in pyrethroid resistance although pyrethroid metabolism has not been observed Riveron et al 2014b).…”
Section: Gene Amplifications Associated With Pyrethroid Resistancementioning
confidence: 99%
“…However, DDT is still being used today for malarial control in many parts of the world including Zimbabwe [3,13]. In A. gambiae an increased rate of DDT dehydrochlorination ( Figure 1) in the resistant strain is associated with an increase in GSTexpression [12]. It has now been shown that AgGSTE2 has very high DDT dehydrochlorinase activity by expressing this isoform in Escherichia coli [2].…”
Section: Introductionmentioning
confidence: 99%
“…Insect GSTs have been classified into six classes: d, 1, s, u, v, and j [11]. The d and 1-class GSTs have been associated with detoxification of various insecticides [12]. An gambiae GSTs are of particular interest because of their involvement in resistance to DDT [1,1,1-trichloro-2,2-bis-p(-chlorophenyl)ethane].…”
Section: Introductionmentioning
confidence: 99%